The individual relationship between atrial fibrillation sources from CARTOFINDER mapping and atrial cardiomyopathy: The catch me if you can trial. - Guckel, Denise; Piran, Misagh; Bergau, Leonard; Hamriti, Mustapha El; Fink, Thomas; Sciacca, Vanessa; Reil, Jan‐Christian; Braun, Martin; Khalaph, Moneeb; Imnadze, Guram; Kramer, Katharina; Friedrich, Sarah; et al. (Pacing & Clinical Electrophysiology, 2023)
Background: Targeting individual sources identified during atrial fibrillation (AF) has been used as an ablation strategy with varying results. Objective: Aim of this study was to evaluate the relationship between regions of interest (ROIs) from CARTOFINDER (CF) mapping and atrial cardiomyopathy from late gadolinium enhancement (LGE) cardiovascular magnetic resonance imaging (CMR). Methods: Twenty consecutive patients underwent index catheter ablation for persistent AF (PERS AF). Pre‐processed LGE CMR images were merged with the results from CF mapping to visualize harboring regions for focal and rotational activities. Atrial cardiomyopathy was classified based on the four Utah stages. Results: Procedural success was achieved in all patients (n = 20, 100%). LGE CMR revealed an intermediate amount of 21.41% ± 6.32% for LA fibrosis. ROIs were identified in all patients (mean no ROIs per patient n = 416.45 ± 204.57). A tendency towards a positive correlation between the total amount of atrial cardiomyopathy and the total number of ROIs per patient (regression coefficient, β = 10.86, p =.15) was observed. The degree of fibrosis and the presence of ROIs per segment showed no consistent spatial correlation (posterior: β = 0.36, p‐value (p) =.24; anterior: β = −0.08, p =.54; lateral: β = 0.31, p = 39; septal: β = −0.12; p =.66; right PVs: β = 0.34, p =.27; left PVs: β = 0.07, p =.79; LAA: β = −0.91, p =.12). 12 months AF‐free survival was 70% (n = 14) after ablation. Conclusion: The presence of ROIs from CF mapping was not directly associated with the extent and location of fibrosis. Further studies evaluating the relationship between focal and rotational activity and atrial cardiomyopathy are mandatory.